Analyzing the Contribution of Social Microfinance to Rural Financial Progress: Entrepreneurial and Social Dimensions in a Developing Nation - Abid Hossain Shawon (Indus Journal of Social Sciences, 2025)
Rural Financial development requires a comprehensive approach that addresses both immediate needs and structural challenges in an emerging economy. By focusing on economic empowerment and social protection, social microfinances are trying to create an environment where individuals and communities can not only escape poverty but also achieve sustainable growth and prosperity. This study examines the impact of social microfinance on rural development and poverty alleviation. The research also investigates key theoretical frameworks, including rural financial and institutional theory, and social capital theory, to assess the effectiveness of rural social microfinance institutions for sustainable development in this region. Utilizing secondary data from the Center for financial inclusion, spanning from 2019 to 2023. Through empirical analysis, the study identifies that critical financial component such as, institutional social performance, operational scale, information transparency, and the ratio of gross loan portfolios to total assets positively influence sustainable rural development outcomes. By combining both theoretical perspectives and empirical findings, this research underscores the dual objectives of social microfinance in Bangladesh, balancing social welfare goals with entrepreneurial strategies. The findings suggest that when rural social microfinance institutions operate with a social enterprise model, that not only significantly contribute to poverty reduction efforts but also ensure sustainable development without relying on subsidies.